A pluralistic approach to public policy: the case of the OECD's New Approaches to Economic Challenges initiative. (2018) - Cerna, Lucie; Hynes, William
The global financial crisis highlighted the need for international institutions to change, adapt and learn. The New Approaches to Economic Challenges (NAEC) initiative provides an important example of a strategic response to the crisis by the Organisation for Economic Cooperation and Development (OECD). NAEC proposes new economic thinking, challenges traditional assumptions, promotes and supports the adoption of pluralism. Drawing on the framework used by Laybourn-Langton and Jacobs (2018), this paper argues that the OECD has slowly embraced pluralism in response to the crisis, and changes can be characterised as a partial paradigm shift. However, the impact of NAEC as assessed by the adoption of pluralism in country reviews and flagship publications has been uneven; and the OECD rather than pushing for a more radical reframing of economic policy is extending and modifying the existing economic framework.